2018
DOI: 10.1016/j.pjnns.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the effects of steroid treatment on the tumor and peritumoral edema by DWI and MR spectroscopy in brain tumors

Abstract: Dexamethasone has no significant effect on the volume of peritumoral edema in glial tumor and metastasis. Moreover, dexamethasone increases the fluid movements in low grade gliomas and metastases, decreases in high grade gliomas. However, more comprehensive clinical studies are needed to show the effects of dexamethasone on brain tumors and peritumoral edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
0
24
1
Order By: Relevance
“…Our results indicate that—after adjustment for volume and the number of individual BM—treatment with GC leads to decreasing VE volumes in large and higher numbers of BM. In contrast, we found 3 former studies propagating no effect of GC administration on VE size (8, 10, 11). This might be due to measurement errors for small BM (according to the formula for volume of a sphere, little changes of diameter lead to significant volume changes) or GC may be ineffective until the VE exceeds a certain volume threshold what we consider less likely.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Our results indicate that—after adjustment for volume and the number of individual BM—treatment with GC leads to decreasing VE volumes in large and higher numbers of BM. In contrast, we found 3 former studies propagating no effect of GC administration on VE size (8, 10, 11). This might be due to measurement errors for small BM (according to the formula for volume of a sphere, little changes of diameter lead to significant volume changes) or GC may be ineffective until the VE exceeds a certain volume threshold what we consider less likely.…”
Section: Discussioncontrasting
confidence: 77%
“…Prior reports on the radiographic effect of GC in BM patients showed ambiguous results: whereas two studies demonstrated reduced VE size after GC administration in 3 and 13 BM patients, three other studies were not able to detect significant differences in VE volume in 4, 7, and 4 BM patients (711). Most patients presenting with clinical symptoms due to mass effect of BM receive GC immediately in the emergency room or even before referral to our academic medical center.…”
Section: Introductionmentioning
confidence: 88%
“…A number of studies have demonstrated DEX effectiveness in management of patients with brain peri-tumor oedema by ameliorating the symptoms associated with vasogenic oedema and intracranial high pressure within 48 h of treatment (Galicich et al, 1961; Hossmann et al, 1983; Ostergaard et al, 1999; Sinha et al, 2004; Dietrich et al, 2011; Kostaras et al, 2014). An excellent technique for monitoring tumor-related oedema in patients is magnetic resonance imaging (MRI) that allows the evaluation of various water diffusion parameters (Yamasaki et al, 2012; Bode et al, 2006; Kural et al, 2018). Using diffusion tensor imaging, Sinha et al (2004) examined individuals with intracranial tumors and observed a significant reduction in the mean diffusivity of brain oedema after 48–72 h post-DEX treatment.…”
Section: Dex Therapy In Gbmmentioning
confidence: 99%
“…Using diffusion tensor imaging, Sinha et al (2004) examined individuals with intracranial tumors and observed a significant reduction in the mean diffusivity of brain oedema after 48–72 h post-DEX treatment. However, a recent study conducted in 28 patients with different degrees of glioma, brain metastases and neurological deficits, reported that DEX had no significant effect on the volume of peritumoral oedema in 19 patients, while some improvements were observed in the remaining (Kural et al, 2018). Given the very frequent use of DEX in GBM therapy and the controversies concerning its effects there is now a renewed interest to evaluate the correlation between the use of this drug and the overall survival (OS) rate of treated patients.…”
Section: Dex Therapy In Gbmmentioning
confidence: 99%
“…In the context of malignant brain tumors, it is used to control peritumoral edema and alleviate symptoms due to high intracranial pressure (ICP) or focal neurologic symptoms [2]. While symptomatic improvement is usually seen within 24 to 72 h [3, 4], the use of DXM is associated with a variety of adverse events including muscular weakness, hyperglycemia, cushingoid symptoms, mental disorders, and gastrointestinal ulceration [3].…”
Section: Introductionmentioning
confidence: 99%